1986
DOI: 10.1007/bf00218073
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes in the lysosomal vacuolar system of rat hepatocytes during short-term starvation

Abstract: Ultrastructural morphometric analysis was used to study time-dependent variations in macro- and microautophagy in rat hepatocytes. Except during periods of short-term starvation for up to 24 h, animals were kept under standardized conditions of food intake. In hepatocytes of meal-fed rats the volume fraction of macroautophagic vacuoles is significantly higher at 23:00 h, i.e., immediately before food intake, compared to 11:00 h, i.e., 12 h following feeding. During fasting, macroautophagy drops to a low level.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

1988
1988
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 18 publications
1
30
0
1
Order By: Relevance
“…56 In rat myocardial cells, the appearance of autophagic vacuoles was observed as late as 2 days after the onset of starvation, indicating a delayed lysosomal response in the process of protein degradation. 54 By contrast, in rat hepatocytes microautophagy (as determined by the measurement of [ 14 C]valine release from degradation of radiolabeled long-lived proteins) was a rather prominent feature during short-term starvation (12-24 h or sometimes up to 48 h) (Fig. 2C).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 89%
See 3 more Smart Citations
“…56 In rat myocardial cells, the appearance of autophagic vacuoles was observed as late as 2 days after the onset of starvation, indicating a delayed lysosomal response in the process of protein degradation. 54 By contrast, in rat hepatocytes microautophagy (as determined by the measurement of [ 14 C]valine release from degradation of radiolabeled long-lived proteins) was a rather prominent feature during short-term starvation (12-24 h or sometimes up to 48 h) (Fig. 2C).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 89%
“…Several studies highlight a range of findings including: (1) that lysosomes show microautophagy activity in vitro, which may be a mechanism for degradation of soluble cytoplasmic constituents in vivo, 51 (2) a lysosomal wrapping mechanism having features resembling those of microautophagy, 6,52 (3) changes in microautophagy apparently related to intrinsic alterations within cells (e.g., liver protein content, rates of protein synthesis and degradation, volumes of lysosomal-vacuolar components), 53 and (4) characterization of starvation-induced microautophagic vacuoles. 54 Glaumann and colleagues 51 showed that isolated rat liver lysosomes incubated with Percoll particles in vitro contain a number of vesicles, some of which contain (one or more) Percoll particles plus surrounding fluid. Percoll particles can sometimes be seen free in the lysosomal matrix, presumably 'released' from the vesicle by degradation of the vesicle membrane.…”
Section: Microautophagy-mediated Degradation Pathways In Mammalian Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…During microautophagy, portions of the cytoplasm are taken up directly by the lysosomes by invagination of their membranes (Ahlberg et al, 1982;Mortimore et al, 1983Mortimore et al, , 1988ade Waal et al, 1986). Microautophagosomes are formed, but they are inside the lysosomes, where they are rapidly degraded.…”
Section: Microautophagymentioning
confidence: 99%